2011
DOI: 10.1016/j.ejcts.2011.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of new nodal classifications for non-small-cell lung cancer based on the number and ratio of metastatic lymph nodes

Abstract: The LNR followed by the number of metastatic LNs may be more effective prognostic indicators than the current nodal classification based on the location of metastatic LNs. For the future revision, the number of metastatic LNs and LNR should be evaluated as indicators for the nodal classification of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 23 publications
2
35
1
Order By: Relevance
“…Indeed, the definition of Meacci et al [12] represents the LNR, as does the definition provided by Dooms et al [11]. Nevertheless, as previously reported by our team and others [4,5,8,9,14], in our study, the LNR remains an independent prognostic factor for OS (OR 0.43, P < 0.01). Because, in multivariate analysis, the LNR remained independent from microscopic N2, we again recommend that the LNR should be taken in account when choosing adjuvant treatment, as previously published.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Indeed, the definition of Meacci et al [12] represents the LNR, as does the definition provided by Dooms et al [11]. Nevertheless, as previously reported by our team and others [4,5,8,9,14], in our study, the LNR remains an independent prognostic factor for OS (OR 0.43, P < 0.01). Because, in multivariate analysis, the LNR remained independent from microscopic N2, we again recommend that the LNR should be taken in account when choosing adjuvant treatment, as previously published.…”
Section: Discussioncontrasting
confidence: 41%
“…Indeed, pN2 disease represents an extremely diverse group of patients. Furthermore, several previously published case series have shown that among pN2 patients, prognosis and OS are very different according to the levels of nodal involvement (uni-or multistation), the lymph node ratio (LNR) or the presence of skip metastases [4][5][6][7]. Furthermore, it seems that according to the subtype of pN2, patients could benefit from different types of adjuvant treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous reports in NSCLC. [12][13][14][15] In contrast to most previous reports, we limited our study to patients diagnosed since 1998, after PET and integrated PET/CT was introduced into clinical practice. 18 The use of PET, and particularly integrated PET/CT, is known to result in more accurate nodal staging of NSCLC 19,20 and reduces the number of thoracotomies and futile thoracotomies.…”
Section: Discussionmentioning
confidence: 99%
“…The LNR has been shown to be prognostic in multiple malignancies, including breast cancer, 9 colon cancer, 10 and melanoma. 11 It has been shown to be prognostic in NSCLC, [12][13][14][15] but the majority of these studies have included patients diagnosed in the era before positron emission tomography (PET) or integrated PET/computer tomography (PET/CT). Furthermore, the LNR has been shown to be predictive of PORT benefit in oral cavity squamous cell carcinoma (SCC).…”
mentioning
confidence: 99%
“…In particular, LNR was a more valuable prognostic factor for patients who suffer from solid malignancies. Increasing evidence suggested that lower LNR was closely relevant to improved survival for breast cancer 17–19, lung cancer 20, colon cancer 21, 22, and other carcinoma 23–26. In specifically, many studies had demonstrated that the LNR was useful in estimating prognosis and should be conjunct with the absolute number of positive lymph nodes in making the right treatment decisions for breast cancer 18, 19.…”
Section: Introductionmentioning
confidence: 99%